Intussusception in the Setting of an Ulcerative Colitis Flare. (30th May 2022) - Abed, Varag; Faber, Alexis; Jageka, Cristina; Goleniak, Ryan; Fadel, Raef
Abstract : Intussusception is an extraordinary cause of acute abdomen in adults and has been defined as the telescoping of a bowel segment into the lumen of an adjacent segment. A 43-year-old female presented to our hospital's emergency department (ED) with 10+ episodes of bloody diarrhea per day, left-sided abdominal pain, and the inability to tolerate oral intake for one month. She was initially diagnosed with ulcerative colitis (UC) ten years ago and is currently on mesalamine oral and enema therapy. She presented to our gastroenterology clinic two weeks after the beginning of her flare and was started on prednisone 40 mg daily. This did not improve her symptoms, and she presented to the ED two weeks later. She underwent a computed tomography (CT) abdomen/pelvis which revealed intussusception in the left hemiabdomen with no definite lead point measuring 5.6 cm in the craniocaudal dimension with pneumatosis and no evidence of bowel obstruction. There were no other significant laboratory abnormalities. Acute care surgery was consulted and suggested obtaining a CT enterography for further evaluation which showed spontaneous resolution of intussusception with no evidence of pneumatosis, portal venous gas, or intraperitoneal free air. She reports that following oral contrast intake, she "felt movement and relaxation" in her abdomen with substantial pain relief. Infectious workup was negative, and therapy was initiated with intravenous steroids. In conclusion, intussusception has been very rarely reported in patients with UC with the most common treatment being surgical resection. However, conservative management in the absence of bowel obstruction can be attempted.